Analysis of Differences Between Groups of Locomotive Crew Drivers With Different Degrees of Ability to Arbitrarily Regulate Their Functional State - N. V. Shcherbina (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The effectiveness of biofeedback based on the electrodermal activity of the skin for the development of the relaxation skill of drivers and assistants of drivers of locomotive crews of the Belarusian Railways was investigated. The experiment was carried out on the basis of the office of the psychological service of the Motor Car Depot in Minsk. A personal computer and a NeuroDog hardware and software complex were used as equipment for the biofeedback training. Based on the results of the biofeedback training, three groups of drivers were identified with varying degrees of successful development of the relaxation skill. We analyzed the differences in psychophysiological and personal characteristics between three groups of test drivers and locomotive crew assistants with varying degrees of ability to voluntarily regulate their functional state. For the analysis, we used the data of psychophysiological examination using the UPDK-MK complex for professional psychophysiological examination and selection of railway workers (Neurokom, Russia) and data obtained by the method of functional biocontrol with biofeedback (NeuroDog, Neurokom, Russia). To identify differences between the groups of subjects, the nonparametric Kruskal – Wallis H-test was used. The calculations were performed in the electronic package Statistica 10.0. Statistically significant differences are shown between groups with different degrees of success in developing the relaxation skill by indicators: concentration of attention, the sixth octant of intrapersonal relationships “dependent – obedientˮ, the time to complete the task of assessing emotional stability, and factor G of the methodology of RB Cattell “low – high normative behaviorˮ.